Homocysteine(HCY), a novel biomarker for predicting irreversible transmural intestinal necrosis in patients with adhesive small bowel obstruction: results from a prospective observational study - Youlong Zhu; Ruming Liu; Xuan Geng; Dakun Li; Bin Quan; Feifei Kong; Defei Hong (World Journal of Emergency Surgery)
Abstract Background Whether elevated homocysteine level is causally associated with small bowel necrosis remains unestablished. We conducted a prospective observational study to analyze the value of serum homocysteine (HCY) in predicting irreversible transmural intestinal necrosis (ITIN) of adhesive small bowel obstruction (ASBO). Methods This prospective observational study was performed between Feb 2023 and Feb 2025 in patients with adhesive small bowel obstruction. The primary outcome was the occurrence of ITIN. The serum levels of different biomarkers in different groups were calculated and compared. Univariable analysis and multivariable analysis were used to assess the association between different biomarkers and ITIN. The Receiver Operating Characteristic Curve (ROC) was used to assess the value for predicting ITIN. Results The patients comprised 129(58.37%) male and 92(41.63%) female with a median age of 70(60–78)(range 18–85 years). Of the 221 patients included, 88(39.82%) received non-operative treatment, and 133(60.18%) underwent surgery. Intestinal resection and ITIN concerned 89(66.92%) and 68(51.13%) of patients who underwent surgery, respectively. Patients underwent surgery had significantly higher serum levels of HCY, ENDOTOXIN, IL-5, IL-6, Hs-CRP, IL-1β, and PCT (p<0.0001, respectively) than patients receiving non-operative treatment. The levels of the above seven markers (p<0.05, respectively) in patients with ITIN were significantly higher than in patients with non-necrosis. Univariable analysis and multivariable analysis showed that HCY、ENDOTOXIN and Hs-CRP were independent predictors for small bowel necrosis (odds ratio = 1.420, 1.061 and 1.032; p = 0 0.000, p = 0.001 and, p = 0.019, respectively). The AUC of HCY (0.9253, p<0.0001) was higher compared with ENDOTOXIN (0.8291, p<0.0001) and Hs-CRP (0.7023, p<0.0001). HCY had highest sensitivity (89.71%) and specificity (83.03%) compared with ENDOTOXIN (82.83%, 62.08%) and CRP (73.53%, 50.77%) for predicting small bowel necrosis. The serum HCY cutoff level for the diagnosis of small bowel necrosis was 15.53µmol/L. Conclusions This study provides compelling evidence that homocysteine (HCY) levels can be a useful predictor of irreversible transmural intestinal necrosis that necessitates surgical resection in the setting of adhesive small bowel obstruction. Close monitoring of the HCY serum level could help avoid unnecessary laparotomy and resection, as well as complications due to unnnecessary surgery, and potentially decrease overall mortality rates.